Influencia da aprendizagem organizacional e do capital intelectual na competitividade e mortalidade empresarial: um estudo sobre os participantes do Programa Bom Negócio Paraná. - Santos, Ariane dos (2016)
The objective of this study is to investigate the influence of organizational learning and intellectual capital on competitiveness and business mortality of organizations participating in the Bom Negócio Paraná Program. The importance of this study is related to the theoretical, empirical and social contributions it brings to the scientific community and society. The study is positivist; with quantitative and descriptive approach and was conducted through desk research and a survey applied to a sample of 266 entrepreneurs with a response rate of 60% of the sample enabled by the nucleus of Cascavel. The questionnaire was composed of indicators from three different authors: Steil (2002), Bontis (1999) and Gold, Malhotra e Segars (2001). To examine the hypothesis of this study and validity of the model, it was adopted the Partial Least Square PLS statistical analysis proposed by Wold (1966), based on the methodology of Dal Vesco, Popik e Beuren (2012). In general, the results showed that the elements of organizational learning when working in isolation are not capable of generating competitive advantage or reducing business mortality rates. Regarding the intellectual capital, when the company invests in any one of its elements it can contribute to increase competitiveness, although the elements of intellectual capital by themselves are not enough to cause business death. This research also found that business competitiveness affects negatively business mortality. By the results of the analysis of the variables relationships considered in this study, it was concluded that the results are in accordance with the low business mortality rate after PBNP capacitation of entrepreneurs. As suggestions for future work, we suggest the application of this model in other PBNP centres in the state of Paraná, and the comparison of results obtained by this model between classes trained in person and via distance mode.